Gastrointestinal Nematode Control in Lithuanian Sheep Farms: Insights from a Questionnaire Survey - Agnė Beleckė; Tomas Kupčinskas; Inga Stadalienė; Rasa Adomkienė; Saulius Petkevičius (Animals)
Anthelmintic resistance (AR) in gastrointestinal nematodes is a growing global concern that threatens effective parasite control in livestock farming. This study aimed to assess gastrointestinal nematode (GIN) control practices and identify risk factors associated with AR development on Lithuanian sheep farms. A cross-sectional survey was conducted between 2022 and 2023 among 71 members of the Lithuanian Sheep Breeders Association, covering farm management, grazing, and deworming practices. Anthelmintics were used by 90.2% of farmers, with most treating their flocks twice a year. Only 18.3% of farmers performed parasitological testing to guide treatments, with significantly more organic farms applying this approach than traditional farms. Treatment frequencies were significantly higher in traditional farms. Most farmers (45.1%) relied on the visual appraisal of sheep weight for dosing, while 35.2% dosed according to the weight of a medium-sized animal. Macrocyclic lactones were the most commonly used anthelmintics (50.7%). Quarantine procedures for new animals were implemented by less than half of the farmers (44.4%), while others treated without isolation (56.6%). These findings indicate reliance on non-strategic parasite control methods and limited use of diagnostics, highlighting the need for improved farmer education to promote sustainable parasite control and reduce AR risk in Lithuanian sheep farms.